2018
DOI: 10.1053/j.gastro.2018.03.058
|View full text |Cite
|
Sign up to set email alerts
|

In Inflamed Intestinal Tissues and Epithelial Cells, Interleukin 22 Signaling Increases Expression of H19 Long Noncoding RNA, Which Promotes Mucosal Regeneration

Abstract: The level of lncRNA H19 is increased in inflamed intestinal tissues from mice and patients. The inflammatory cytokine IL22 induces expression of H19 in IECs, which is required for intestinal epithelial proliferation and mucosal healing. H19 lncRNA appears to inhibit p53 protein and microRNA 34a and let-7 to promote proliferation of IECs and epithelial regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
112
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(119 citation statements)
references
References 35 publications
7
112
0
Order By: Relevance
“…lncRNAs have essential biological functions, and H19 is one of the few well‐characterized lncRNAs, which is an imprinted and maternally expressed transcript . Aberrant expression of H19 has been associated with numerous disease conditions . The current study showed that BA patients had significantly higher levels of H19 mRNA in livers when compared to control subjects, which indicates that H19 may play a role in the pathogenesis of BA.…”
Section: Discussionsupporting
confidence: 51%
“…lncRNAs have essential biological functions, and H19 is one of the few well‐characterized lncRNAs, which is an imprinted and maternally expressed transcript . Aberrant expression of H19 has been associated with numerous disease conditions . The current study showed that BA patients had significantly higher levels of H19 mRNA in livers when compared to control subjects, which indicates that H19 may play a role in the pathogenesis of BA.…”
Section: Discussionsupporting
confidence: 51%
“…5B and 5C), and it required STAT3. Previous study demonstrated IL-22 activates expression of lncRNA H19 in intestinal epithelial cells (IECs), which is required for IECs healing and regeneration [28]. In the current study, we hypothesize that IL-22 drives metabolic reprogramming to maintain mitochondrial fitness and treat liver injury through lncRNA H19.…”
Section: The Induction Of Lncrna H19 By Il-22 Activates Mtor Signalinmentioning
confidence: 76%
“…In the current study, we first demonstrated that IL-22 drives a metabolic adaptive reprogramming to maintain mitochondrial fitness, which in turn regulated hepatocellular metabolic processes. Further data indicated that IL-22 was capable of upregulating lncRNA H19, AMPK, mTOR and AKT in hepatocytes, key regulators of cell proliferation and epithelial wound healing, to eliminate dysfunctional mitochondria and opening up a new arena for IL-22 mediated mechanisms of action [28,30]. Together, these data illustrated that the induction of metabolic reprogramming in hepatocytes could attribute to IL-22-mediated liver protective activities.…”
Section: Discussionmentioning
confidence: 99%
“…This would allow for finer regulation of AQP3 expression by competing for miR‐874 and may also improve intestinal barrier dysfunction. Geng et al found that under normal conditions, H19 is transcriptionally silent in the small intestine of adult mice. However, it becomes strongly activated after LPS treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Geng et al 20 shown that fasting for 48 hours inhibits small intestinal mucosal growth in mice. Importantly, Xiao et al 12 PRE1 has also previously been shown to regulate the expression of CCND1.…”
mentioning
confidence: 99%